Public administration sustainability and its organizational basis. (June 2021) - Trondal, Jarle
Benefiting from a novel data set spanning nearly half a century, this study probes the sustainability of public governance. Theoretically, it examines how sustainable public governance rests on its organizational fabric. The study illuminates how organizational factors systematically influence decision-making behaviour and thus public governance sustainability. Moreover, the study argues that since organizational structure is amendable to deliberate manipulative change, it may thus be an important design instrument of the context of choice in public governance. Accordingly, the article offers an avenue to build bridges between the academic and practitioner worlds of public administration. Empirically and methodologically, the study offers: a novel large- N (13, 173) and longitudinal data set that spans five observation points in 1976, 1986, 1996, 2006 and 2016; nine surveys at ministry and agency levels; and several generations of government officials. Taken together, the data set demonstrates that both administrative sustainability in public administration and sustainable public governance rest on its organizational fabric. Points for practitioners: A sustainable public administration is a necessary condition for public service delivery. Based on observations that span 40 years (1976 to 2016), this study offers an opportunity to systematically trace public governance processes over half a century. Second, this study examines how sustainable public governance rests on its organizational fabric. Organizational factors systematically influence decision-making behaviour and arguably influence administrative governance. Moreover, organizational structure is amendable to deliberate manipulative change and may thus be an important design instrument of the context of choice in public governance. As such, the article offers an avenue to build bridges between the academic and practitioner worlds of public administration.